Makna Simbolik Natas Banyang Pada Upacara Pernikahan Adat Dayak Maanyan di Barito Timur Dan Implikasinya Terhadap Pembelajaran Sastra di SMA - Elin Widia; Petrus Poerwadi; Misnawati Misnawati; Patricia Cuesdeyeni; Lazarus Linarto (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2023)
The purpose of this study was to obtain the symbolic meaning of Natas Banyang at the Maanyan Dayak Traditional wedding ceremony in east Barito and its implications for literatur learning in SMA. The purpose of this study was to describe: (1) the symbolic meaning of events in natas banyang (2) symbolic meaning of objects in natas banyang (3) the symbolic meaning of language in natas banyang (4) implications for learning literature in high school class X. This study uses a qualitative opproach method. The data source for this research is the natas banyang process and interviewing traditional mantir. The objects of this study are all the symbolic meanings of natas banyang at the Maanyan Dayak traditional wedding ceremony in east Barito. The results of this study areas follows. (1) The symbolic meaning of events in natas banyang (2) The symbolic meaning of objects used in natas banyang (3) the symbolc meaning of language in natas banyang (4) Used in teaching literature for class X SMA, In accordance with KD 4.1 Interpreting the meaning of pantun texts both oral or written. Indicator 4.1. Identifying the linguistic elements of the pantun texts both oral or written. Indicator 4.1.1 Identefying the linguistic elements of the pantun text 4.1.2 interpret the pantun text. natas banyang at the maanyan Dayak traditional wedding ceremony in east Barito which aims to develop knowledge in regional culture.